Early Results of Ponseti Technique for Idiopathic Congenital Talipes Equinovarus (Medical Forum Monthly, 2024)
Clubfoot or congenital talipes equinovarus is one of the most common congenital anomaly affecting the lower limb. The exact cause is unknown and a number of theories have been postulated to explain its origin. Congenital talipes equinovarus affects both sexes and may be unilateral or bilateral. Clubfoot is sometimes associated with Arthrogryposis multiplex congenita, spina bifida, meningomyelocele and muscular dystrophies. Objective: This study was conducted to determine the early results of ponseti technique for idiopathic congenital talipes equinovarus.Study Design: Observational (Follow-up) Study.Place and Duration of Study: This study was conducted at orthopedic B-Unit of Ayub Teaching Hospital Abbottabad from 1st April 2009 to 30th September 2009.Materials and Methods: Thirty (30) patients from either gender with age from birth to 06 months of age attending the outpatient department of Orthopedic B-Unit of Ayub Teaching Hospital Abbottabad were included in the study. Results: The patients were ranged in age from birth to o6 months of age, with 17 male (56.7%) and 13 female (43.3%). In our series on follow up, fore foot adduction was detected in 06 cases (20%) and 02 cases had equinus relapse (6.7%) and 03 patients had residual equinus (10%) while bilateral residual equinus was detected in 01 patient (3.3%) and 01 patient had recurrence of deformity (3.3%) for which posteromedial release was done.Conclusion: We concluded that the Ponseti method is a reliable, simple, effective and safe method for the treatment of idiopathic clubfoot deformity.